IMPLEMENTASI FINITE STATE MACHINE PADA GAME TAJWID ADVENTURE - Novia Divarotul Achyum (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2025)
The development of the gaming industry has required developers to create more immersive gaming experiences. In this context, the use of Finite State Machine (FSM) has become a popular and effective solution in managing storylines as well as more structured character development. This article aims to review the basic concepts of FSM and describe its implementation in the game “Tajwid Adventure” as a means of education and entertainment. The application of FSM in this game aims to improve the dynamics of the game and provide a clear structure in the player's journey. This abstract will discuss in detail the basic concepts of FSM applied in the game, highlighting how the use of FSM can improve the quality of the playing experience for players. Through the analysis of the FSM implementation in this game, this article presents a deeper understanding of how the FSM framework can be used to govern the storyline, character behavior, and overall game dynamics. The implementation of FSM in “Tajwid Adventure” brings a positive impact in creating a play experience that is structured, dynamic, and relevant to the expectations of modern players.